Immune‐modified Glasgow prognostic score: A new prognostic marker for head and neck cancer. Issue 11 (23rd August 2022) - Terazawa, Kosuke; Ohashi, Toshimitsu; Shibata, Hirofumi; Ishihara, Takuma; Ogawa, Takenori
Abstract: Background: The modified Glasgow prognostic score (mGPS) includes C‐reactive protein and serum albumin levels and is a useful prognostic tool for malignant tumors. The immune system affects cancer progression and recurrence and treatment response. We hypothesized that increasing the lymphocyte count improves mGPS, and we created a new prognostic marker termed immune‐mGPS (imGPS). Methods: This study included 461 patients with head and neck squamous cell carcinoma (HNSCC). The imGPS was calculated as the conventional mGPS with one additional point for a low lymphocyte count (<1250/μL). Results: Addition of the lymphocyte count to mGPS significantly increased the area under the time‐dependent receiver operating characteristic curve for overall and progression‐free survivals. The added predictive abilities of this tool were supported by improvement in both net reclassification and integrated discrimination. Conclusion: imGPS is a more accurate predictor of clinical outcome in patients with HNSCC than mGPS.